Metformin enhances doxorubicin sensitivity via inhibition of doxorubicin efflux in P‐gp‐overexpressing MCF‐7 cells. (24th August 2017) - Shafiei‐Irannejad, Vahid; Samadi, Nasser; Yousefi, Bahman; Salehi, Roya; Velaei, Kobra; Zarghami, Nosratollah
Abstract : Resistance against chemotherapy is still a major problem in successful cancer treatment in the clinic. Therefore, identifying new compounds with lower side‐effects and higher efficacy is an important approach to overcome multidrug resistance (MDR). Here, we investigated the activity and possible mechanism of the antidiabetic drug, metformin, in human doxorubicin (DOX)‐resistant breast cancer (MCF‐7/DOX) cells. The effect of metformin on the cytotoxicity of DOX was evaluated by MTT assay. The P‐gp mRNA/protein expression levels following treatment with metformin were determined using real‐time polymerase chain reaction and Western blot analysis, respectively. Intracellular rhodamine 123 accumulation assay was performed to evaluate the P‐gp function. Cellular ATP content was determined using ATP assay kit. The effect of metformin on DOX‐induced apoptosis was evaluated by annexin V/FITC assay. Exposure to metformin considerably enhanced the cytotoxicity of DOX. Metformin had no substantial effect on P‐gp expression, while the activity of P‐gp and intracellular ATP content decreased with metformin treatment in a dose‐dependent manner. Furthermore, metformin significantly increased the DOX‐induced apoptosis. These results indicate that metformin could reverse MDR in breast cancer cells by reducing P‐gp activity. Therefore, metformin can be suggested as a potent adjuvant in breast cancer chemotherapy. Abstract : The activity and possible anticancer mechanism of antidiabetic drug, metformin, in doxorubicin‐resistant MCF‐7 (MCF‐7/DOX) cells was investigated. Metformin sensitized MCF‐7/DOX cells and increased apoptosis via inhibition of P‐gp activity and ATP depletion, with no substantial effect on P‐gp expression.